Skånska småstadskommuner söker hjälpbehövande medborgare En kritisk diskursanalys utav missbruks- och beroendeinformationen på skånska kommuners hemsidor - Olson,Fredrik (2025)
The Swedish system of helping with addiction-related problems is based upon municipalities' and regional hospitals' lawful responsibilities towards its citizens and patients. This thesis looks at five of the southernmost regions of Skånes municipalities' webpages, that serve to inform and attract people who have issues with substance abuse and the side effects this has on their close ones. Through Fairclough´s critical discourse analysis, I have strived to see how the language on webpages both creates, and sustains, the discourse about addicts and how the municipalities portray themselves as caretakers and helpers in different ways to the public. The findings show that the municipalities are using three different types of discourse: individualization, professionality, and judicial. Both interdiscoursivity and other types of intertextuality and manifest intertextuality are found. Showing they create a wide range of subject positioning towards the targeted reader. The readers visiting the webpages are described in varied forms of subject positioning both to individual close relationships and towards social services and their varied professions. The study shows an ambivalence between whether the municipalities do want to attract their citizens in the pursuit of helping them, or as a means of pushing them away from seeking help.
Keywords: municipiality; substance abuse; webpage; communication; discourse; critical discourse analysis; interdiscoursivity; manifest intertextuality; subject positioning